Executive policymaking : the role of the OMB in the presidency - Bose, Meenekshi, 1970-; Rudalevige, Andrew, 1968- (Brookings Institution Press, 2020)
"The contributors take a deep look into the Office of Management and Budget (OMB), one of the federal government's most important and powerful agencies. It's also one of the least-known government agencies among the general public. The book describes why the office is so important and why both scholars and citizens should know more about what it does. The predecessor to the modern OMB was founded in 1921, as the Bureau of the Budget within the Treasury Department. President Franklin D. Roosevelt moved it in 1939 into the Executive Office of the President, where it's been ever since. The office received its current name in 1970, during the Nixon administration. For most people who know about it, the OMB's only apparent job is to supervise preparation of the president's annual budget request to Congress. That job, in itself, gives the office tremendous influence within the executive branch. But OMB has other responsibilities that give it a central role in how the federal government functions on a daily basis. OMB reviews all of the administration's legislative proposals and the president's executive orders. It oversees the development and implementation of nearly all government management initiatives. The office also analyses the costs and benefits of major government regulations, thus giving it great sway over government actions that affect nearly every person and business in America. One question facing voters in the 2020 elections will be how well the executive branch has carried out the president's promises; a major aspect of that question centers around the wider work of the OMB. This book will help members of the public, as well as scholars and other experts, answer that question"--